Preferences over Taxation of High-Income Individuals: Evidence from a Survey Experiment - Dirk Engelmann; Eckhard Janeba; Lydia Mechtenberg; Nils Wehrhöfer (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Mobility of high-income individuals across borders puts pressure on governments to lower taxes. A central tenet of the corresponding textbook argument is that mobile individuals react to tax differentials through migration, and in turn immobile individuals vote for lower taxes. We investigate to which extent this argument is complete. In particular, political ideology may influence voting on taxes. We vary mobility and foreign taxes in a survey experiment within the German Internet Panel (GIP), with more than 3,000 individuals participating. We find that while the treatment effects qualitatively confirm model predictions how voters take mobility of high-income earners into account when choosing domestic taxes, ideology matters: left-leaning high-income individuals choose higher taxes and emigrate less frequently than right-leaning ones. These findings are in line with the comparative-static predictions of a simple model of inequality aversion when the aversion parameters vary with ideology.
Keywords: D72; F22; H21; 330; taxation; mobility; ideology; survey experiments